Function and regulation of the CD95 (APO-1/Fas) ligand in the immune system - Li-Weber, Min; Krammer, Peter H. (Seminars in immunology, 2003)
CD95/CD95L mediated apoptosis is an important mechanism of immune homeostasis. It is instrumental for termination of an immune response and mainly be involved in peripheral tolerance. Dysregulation of the CD95/CD95L system leads to severe diseases. In this review, we present a survey of the role of the CD95/CD95L system in the immune system and, particularly, focus on the signals and transcription factors (NF-AT, Egr, NF-κB, AP-1, c-Myc, Nur77, IRFs, SP-1, ALG-4, RORγt, and CIITA) involved in CD95L expression. It should also be evident from this review that a profound insight into the molecular mechanisms of CD95L activation should allow to explore potential therapeutic means to treat CD95/CD95L-dependent diseases.
Gesehen am 02.03.2021